The effectiveness of calcium electroporation combined with gene electrotransfer of a plasmid encoding IL-12 is tumor type-dependent - Lisec, Barbara; Markelc, Bostjan; Ursic Valentinuzzi, Katja; Sersa, Gregor; Cemazar, Maja (Frontiers in Immunology, 2023)
Introduction In calcium electroporation (CaEP), electroporation enables the cellular uptake of supraphysiological concentrations of Ca2+, causing the induction of cell death. The effectiveness of CaEP has already been evaluated in clinical trials; however, confirmatory preclinical studies are still needed to further elucidate its effectiveness and underlying mechanisms. Here, we tested and compared its efficiency on two different tumor models to electrochemotherapy (ECT) and in combination with gene electrotransfer (GET) of a plasmid encoding interleukin-12 (IL-12). We hypothesized that IL-12 potentiates the antitumor effect of local ablative therapies as CaEP and ECT. Methods The effect of CaEP was tested in vitro as well as in vivo in murine melanoma B16-F10 and murine mammary carcinoma 4T1 in comparison to ECT with bleomycin. Specifically, the treatment efficacy of CaEP with increasing calcium concentrations alone or in combination with IL-12 GET in different treatment protocols was investigated. We closely examined the tumor microenvironment by immunofluorescence staining of immune cells, as well as blood vessels and proliferating cells. Results In vitro, CaEP and ECT with bleomycin reduced cell viability in a dose-dependent manner. We observed no differences in sensitivity between the two cell lines. A dose-dependent response was also observed in vivo; however, the efficacy was better in 4T1 tumors than in B16-F10 tumors. In 4T1 tumors, CaEP with 250 mM Ca resulted in more than 30 days of growth delay, which was comparable to ECT with bleomycin. In contrast, adjuvant peritumoral application of IL-12 GET after CaEP prolonged the survival of B16-F10, but not 4T1-bearing mice. Moreover, CaEP with peritumoral IL-12 GET modified tumor immune cell populations and tumor vasculature. Conclusions Mice bearing 4T1 tumors responded better to CaEP in vivo than mice bearing B16-F10 tumors, even though a similar response was observed in vitro. Namely, one of the most important factors might be involvement of the immune system. This was confirmed by the combination of CaEP or ECT with IL-12 GET, which further enhanced antitumor effectiveness. However, the potentiation of CaEP effectiveness was also highly dependent on tumor type; it was more pronounced in poorly immunogenic B16-F10 tumors compared to moderately immunogenic 4T1 tumors.